Transient Stability Analysis of IEEE-9 Bus Electrical Power System (International Journal of Engineering and Computer Science, 2017)
Power system stability is an important aspect which determines the stability of the system. This paper deals with the rotor angle stability of IEEE 9-bus system consists of three generators and nine buses. To demonstrate the performance of the system, a three phase fault is introduced on different locations. The nature of the rotor angle excitation voltage and speed for all three generators are discussed. As the fault is cleared the system takes its own time to settle down. Keywords: Transient stability, three phase fault, multi machine,